ENHANCING THE RESISTANCE TO HYDROABRASIVE WEAR OF CENTRIFUGAL PUMP IMPELLERS BY STRENGTHENING THE SURFACE LAYER WITH FUNCTIONAL COATINGS (Innovative technologies, 2026)
The article analyzes issues related to improving the operational reliability of centrifugal pumps widely used in the mining industry. It has been established that the primary causes of failures in pumping equipment operating in hydrotransport systems are hydroabrasive wear of impellers, casings, and covers. Based on statistical and experimental data obtained from pump stations of mining enterprises in Uzbekistan, the service life and failure causes of centrifugal pump components were investigated. The research results indicate that up to 70–75% of failures are associated with intensive wear of the surface layer of pump impellers.Methods for extending the service life of pump impellers through strengthening their surface layer with functional coatings are analyzed, and the advantages of cold gas-dynamic spraying technology are scientifically substantiated. Using this approach, metallic and metal–ceramic composite coatings are formed, which increase the resistance of impellers to hydroabrasive and cavitation effects. It is demonstrated that the application of such coatings makes it possible to reduce the operating costs of centrifugal pumps and significantly extend their service life.
Keywords: centrifugal pump; impeller; hydroabrasive wear; functional coating; cold gas-dynamic spraying; hydrotransport; efficiency; operational reliability